Hyperuricemia in Psoriatic Arthritis: Epidemiology, Pathophysiology, and Clinical Implications - Tripolino, Cesare; Ciaffi, Jacopo; Ruscitti, Piero; Giacomelli, Roberto; Meliconi, Riccardo; Ursini, Francesco (Frontiers in Medicine, 2021)
Psoriatic arthritis (PsA) represents the articular component of the systemic psoriatic disease and the extra-cutaneous disorder most frequently found in patients with psoriasis. Besides the articular involvement, PsA is associated with several metabolic abnormalities such as insulin resistance, hypertension, diabetes and hyperuricemia. Uric acid is the final product of purine metabolism and the etiological substrate of gout. Accumulating evidence highlights the emerging role of hyperuricemia as a major cardiovascular risk factor. Moreover, different studies evaluated the interplay between hyperuricemia and psoriatic disease, suggesting that individuals affected by psoriasis or PsA might present higher serum levels of uric acid and that hyperuricemia might affect severity of clinical manifestations and degree of inflammation in PsA patients. In this review, we focus on the bidirectional relationship between uric acid and PsA, analysing how uric acid may be involved in pathogenesis of psoriasis/PsA and how clinical manifestations of PsA and inflammatory mediators are affected by uric acid concentrations. Finally, the effects of anti-rheumatic drugs on uric acid levels and the potential benefit of urate-lowering therapies on psoriasis and PsA were summarized.